2021
DOI: 10.3390/healthcare9101256
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Rural Medical Students Regarding the Future of General Medicine: A Thematic Analysis

Abstract: Although the demand for general physicians has increased in Japan because of its aging population, medical universities primarily provide organ-based education; thus, medical students do not receive sufficient general medical education. The number of residents focusing on general medicine remains low; therefore, to understand the present situation regarding general medicine education, we attempted to clarify the views of medical students and the factors influencing them. In this qualitative study, semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In Japan, family physicians’ educational systems were officially established in 2017 as the nineteenth specialty, following discussions among family physicians, general internal medicine physicians, hospitalists, and primary care physicians [ 8 ]. "General medicine" is the nomenclature for this specialty.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, family physicians’ educational systems were officially established in 2017 as the nineteenth specialty, following discussions among family physicians, general internal medicine physicians, hospitalists, and primary care physicians [ 8 ]. "General medicine" is the nomenclature for this specialty.…”
Section: Editorialmentioning
confidence: 99%
“…To specialize in people as a system, family physicians should collaborate with various organ-specific specialists because less collaboration among the specialists may negatively influence healthcare systems. In the present situation, because of the short history of family medicine in Japan, family physicians may not be relied on by other organ-specific specialists [ 8 , 12 ]. Training in various clinical contexts and continuing high-quality care in family medicine can mitigate the gap between system- and organ-specific specialists, improving older patient care.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the general medicine education offered by Japanese universities has been considered immature, providing medical students little exposure to general medicine and having insufficient related policies. 21 , 22 However, it is unclear how much effort Japanese university general medicine departments (whose personnel have basic medical skills and a high affinity for clinical practice) devote to medical education, particularly undergraduate education. Therefore, this study aimed to clarify the contribution of general medicine departments in Japanese universities to medical education and develop suggestions for future general medicine education at universities.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that students’ perceptions and opinions are important references for the arrangement of educational programs [ 12 , 13 , 14 ], and collaboration between students and clinical faculties at internship hospitals can create effective educational programs [ 15 ]. Instructional media designed from the perspective of participants can help them follow instructions more effectively [ 16 ].…”
Section: Introductionmentioning
confidence: 99%